Tobacco control in Poland—successes and challenges - Jassem, Jacek; Przewoźniak, Krzysztof; Zatoński, Witold (Translational Lung Cancer Research; Vol 3, No 5 (October 21, 2014): Translational Lung Cancer Research [The 14th Central European Lung Cancer Congress (CELCC)], 2014)
For many years, tobacco smoking was the major single avoidable cause of premature mortality in Poland. In the 1970s and 1980s, Poland was a country with an extremely high prevalence of smoking and lung cancer mortality among men in the world. By 1990, over 40% of Polish men died prematurely from smoking-attributed diseases. However, the enforcement of comprehensive tobacco-control measures and programs based on the World Health Organization recommendations and the best practices from other countries, contributed to a spectacular decrease of smoking incidence, particularly in men. This led to dramatic decrease in lung cancer incidence and mortality, and to a substantial improvement in public health in Poland. This article reviews the achievements of tobacco-control in Poland over the past decades and points out current challenges in this field.